Environmental controls of frost cracking revealed through in situ acoustic emission measurements in steep bedrock. Issue 9 (15th May 2013) - Girard, Lucas; Gruber, Stephan; Weber, Samuel; Beutel, Jan
Abstract : [1] Frost cracking, the breakdown of rock by freezing, is one of the most important mechanical weathering processes acting on Earth's surface. Insights on the mechanisms driving frost cracking stem mainly from laboratory and theoretical studies. Transferring insights from such studies to natural conditions, involving jointed bedrock and heterogeneous thermal and hydrological properties, is a major challenge. We address this problem with simultaneous in situ measurements of acoustic emissions, used as proxy of rock damage, and rock temperature/moisture content. The 1 year data set acquired in an Alpine rock wall shows that (1) liquid water content has an important impact on freezing‐induced rock damage, (2) sustained freezing can yield much stronger damage than repeated freeze‐thaw cycling, and (3) that frost cracking occurs over the full range of temperatures measured extending from 0 down to −15°C. These new measurements yield a slightly different picture than previous field studies where ice segregation appears to play an important role. Key Points: Rock liquid water content has an important impact on the freezing-induced damage Sustained freezing can yield stronger damage than repeated freeze-thaw cycling Frost cracking occurs on a wide range of temperatures extending from 0 to -15C